2006
DOI: 10.1152/ajprenal.00204.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic background on nephropathy in diabetic mice

Abstract: With the goal of identifying optimal platforms for developing better models of diabetic nephropathy in mice, we compared renal effects of streptozotocin (STZ)-induced diabetes among five common inbred mouse strains (C57BL/6, MRL/Mp, BALB/c, DBA/2, and 129/SvEv). We also evaluated the renal consequences of chemical and genetic diabetes on the same genetic background (C57BL/6). There was a hierarchical response of blood glucose level to the STZ regimen among the strains (DBA/2 > C57BL/6 > MRL/MP > 129/SvEv > BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
265
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(312 citation statements)
references
References 47 publications
37
265
0
4
Order By: Relevance
“…21,32 The findings clearly demonstrate that reduced eNOS activity enhances glomerular injury in the setting of diabetes, supporting human studies suggesting that eNOS polymorphism and reduced eNOS activity are associated with accelerated diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…21,32 The findings clearly demonstrate that reduced eNOS activity enhances glomerular injury in the setting of diabetes, supporting human studies suggesting that eNOS polymorphism and reduced eNOS activity are associated with accelerated diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 74%
“…Among the inbred strains tested, C57BL/6 strain mice were shown to be resistant to nephropathy (albuminuria). 21,32 Importantly, the present study has demonstrated that insufficient eNOS activity may alter susceptibility of C57BL6 mouse to diabetic glomerular injury, indicating a vital role of eNOS in the development of diabetic nephropathy. Our results in mice support the finding in human diabetes that a predisposition for development of nephropathy is closely associated with eNOS polymorphisms.…”
Section: Discussionmentioning
confidence: 52%
“…These authors found that deletion of the Ace2 gene was associated with the development of albuminuria over time (12 mo of age) in male but not in female mice. In general, it is more difficult to produce albuminuria in female than in male mice (14,25). In this respect, it is noteworthy that in this study we used female db/db mice, because we were not aware of the findings of Oudit et al, which were published just recently (23).…”
Section: Discussionmentioning
confidence: 94%
“…14,15 Briefly, diabetes was induced with intraperitoneal injections of STZ (Calbiochem, San Diego, CA, USA) dissolved in 0.05 M sodium citrate buffer (pH 4.5). Mice received two rounds of injections of 40 mg/(kg day) STZ for 5 consecutive days, first at 8 weeks of age, and then, at 12.…”
Section: Materials and Methods Animals And Sample Preparationsmentioning
confidence: 99%